Chemical properties of moldy grains of sorghum genotypes as influenced by harvesting stages - B.P. KURUNDKAR, S.D. SOMWANSHI* and (Indian Phytopathology, 2008)
Eight sorghum genotypes grown during the year 2002 and infected with grain mold were evaluated to study the chemical properties of moldy grains. Study indicated that crude protein, crude fibre, crude fat, soluble sugars, moisture contents, ash content and tannin content significantly differed in sorghum genotypes. Crude protein content was highest in IS-14384 while crude fibre, crude fat, moisture content and ash content were significantly higher in susceptible check Bulk-Y than other genotypes. Soluble sugar content and tannin content were maximum in PVK-801. Crude protein, soluble sugars, moisture content and tannin content were significantly higher when harvesting was carried out at physiological maturity than at crop maturity. However, crude fibre, crude fat and ash content were significantly higher when harvesting was done at crop maturity than at physiological maturity.